POST METHOD PEDAGOGY AND ITS LEVEL OF STUDY (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
The phenomena of modern globalization and internationalization, entering the world educational space not only help to create a multicultural educational space, but also contribute to its multifaceted development. In this thesis, the research level of post-method pedagogy and the definition of the given term by world scientists are analyzed.